Caerulein induced plasma amino acid decrease: a simple, sensitive, and specific test of pancreatic function. Issue 8 (August 1990) - Gullo, L; Pezzilli, R; Ventrucci, M; Barbara, L
Abstract : We measured total plasma amino acid concentrations before and during pancreatic stimulation with secretin (1 clinical unit/kg/h) and caerulein (50 ng/kg/h) in 28 healthy volunteers, 60 patients with chronic pancreatitis (25 mild to moderate, 35 severe), and 22 patients with non-pancreatic digestive disease. In the healthy volunteers and patients with non-pancreatic digestive disease pancreatic stimulation caused a significant decrease (p less than 0.001) in plasma amino acid concentration, whereas in patients with chronic pancreatitis the decrease did not occur or was only slight. In six healthy volunteers and 24 patients with chronic pancreatitis (nine mild to moderate, 15 severe) repetition of the test using caerulein alone showed no significant differences from combined stimulation. Using the maximal per cent decrease in plasma amino acid concentration as an index of pancreatic function (lower normal limit 14%), 20 of the 25 patients with mild to moderate pancreatitis (80%) and 32 of the 35 with severe pancreatitis (91.4%) had values clearly below normal. The overall sensitivity of the test (86.7%) was significantly greater than that of the pancreolauryl test (64.2%) (p less than 0.02) and that of faecal chymotrypsin (66%) (p less than 0.05). None of the patients with non-pancreatic digestive disease had abnormal values. We conclude that the assessment of the decrease in the plasma amino acid concentration during pancreatic stimulation with secretin and caerulein is a simple, sensitive, and highly specific test of pancreatic function. The data obtained using caerulein stimulation alone suggest that the test can be further simplified, and made less costly, by eliminating the use of secretin.